Angular analysis of the decay B+-> K*(892)(+)mu(+)mu(-) in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2021)
Angular distributions of the decay B+-> K*(892)(+)mu(+)mu(-) are studied using events collected with the CMS detector in root s = 8 TeV proton-proton collisions at the LHC, corresponding to an integrated luminosity of 20.0 fb(-1). The forward-backward asymmetry of the muons and the longitudinal polarization of the K*(892)(+) meson are determined as a function of the square of the dimuon invariant mass. These are the first results from this exclusive decay mode and are in agreement with a standard model prediction.
Keywords: B physics; Hadron-Hadron scattering (experiments)